2022
DOI: 10.4102/aveh.v81i1.742
|View full text |Cite
|
Sign up to set email alerts
|

Decentralised clinical training in optometry: Student perspectives

Abstract: Background: Decentralised clinical training (DCT) allows for training outside of central academic sites to within district-based ones with the expectation of enhanced exposure translating into improved competency of students. Aim: To determine student perspectives and experiences with the DCT model in clinical training for optometry.Setting: Data were collected using an online survey created with Google Forms.Methods: An exploratory, descriptive, case-based design using an online questionnaire consisting of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…[12] It is suggested that DCTP provides broader student exposure to a range of patients in terms of the ecology of healthcare, thereby improving the students' competencies. [13] A review of the current practices of universities that provide teaching and learning through DCTP has revealed that this has typically occurred in the rural context, in primary level facilities, community-based centres and district hospitals. [14,15] Research studies further show that undergraduate medical students, to a large extent, have been at the centre of the implementation and roll-out of DCTP.…”
Section: Researchmentioning
confidence: 99%
“…[12] It is suggested that DCTP provides broader student exposure to a range of patients in terms of the ecology of healthcare, thereby improving the students' competencies. [13] A review of the current practices of universities that provide teaching and learning through DCTP has revealed that this has typically occurred in the rural context, in primary level facilities, community-based centres and district hospitals. [14,15] Research studies further show that undergraduate medical students, to a large extent, have been at the centre of the implementation and roll-out of DCTP.…”
Section: Researchmentioning
confidence: 99%
“…In recent years, students taught through DCTPs have been expanded beyond medicine to include undergraduate students in the multidisciplinary biomedical system of health care, which encompasses nursing, occupational therapy, physiotherapy, and optometry, to name a few. Anecdotal evidence regarding students’ experiences of and perspectives about DCTPs indicates overall positive learning experiences reported by students who are taught using this approach [ 14 , 15 ]. Moreover, students have perceived education through DCTPs as strengthening their responsiveness, preparedness, and relevance as graduates.…”
Section: Introductionmentioning
confidence: 99%